Etnološki in antropološki pogledi na javne prireditve v Sloveniji - Kozorog, Miha (Etnolog. Nova vrsta (Ljubljana), 2014)
This survey article presents the history of ethnological and anthropological literature on public events, starting from the institutionalisation of ethnology in Slovenia. It begins with the question which events should be considered "public events". The author concludes that the term "public" is not always clearly defined, and that the word "event" is not an analytical concept. He therefore dedicates attention to the widest possible selection of authors who wrote about intentionally, i.e. deliberately staged events, accessible to a certain public, not just an organised group. In the second part the author draws attention to ethnographic work, where he considers public events an opportunity to establish a relationship between ethnographers and their informants in the field. Quoting examples from the international literature, he presents a description of fieldwork in Resia, where a team of researchers at first did not manage to establish a relationship with the locals, and only succeeded in doing so because of the relaxed mood on the occasion of a village holiday. This public event thus provided an opportunity to establish connections and assisted the researchers in the fieldwork. However, the ethnography of public events opens up a methodological dilemma: in which way is whatever the researcher observes really an authentic or modified expression of a certain culture? The issue of authenticity has accompanied ethnography for a very long time, and in the field of public events it refers in particular to tourist events. The author comes to the conclusion that the issue indeed excessively burdened Slovene ethnologists, and that they therefore ignored a range of public events whose contents they could not relate to. In a way, they acted as guardians of "correct" performances of "traditions", i.e. more in a technical capacity than in a scientific one. Scientific research considered only one segment of organized public events, i.e. events related to the "customs of the annual cycle". Niko Kuret contributed a classification and paradigm for their research. In accordance with his historical-genealogical model, customs of an obviously older origin (not a modern one) were recorded in different places in Slovene. They were mapped and compared with similar phenomena around Europe and researchers searched for sources about their past forms, which then served to surmise hypotheses on their historical origin. In these endeavours ethnology was heavily preoccupied with the past, while the present was understood as a source of forces hostile to tradition. This among others led to a rescue approach, i.e. positivist recording of ritual practices before they disappeared. There have been few synchronous analyses of public events in the history of ethnology. Angelos Baš, for instance, contributed in the 1970s an analysis of the extensive range of factors which at a certain time in history let to the organisation of horse races in Štajerska; otherwise such analyses became more frequent only from the 1990s onwards. In this period, several researches explored popular music events, political manifestations, and events in the context of tourism, and their researchers simultaneously experienced reflection on their role as co-instigators of the events. The article concludes with a proposal for ethnology and anthropology to dedicate attention not only to the past and present, but also the future, and considers public events as a time and space suitable for the production of something new, where public ethnography can assist in creating a better future.
Keywords: ethnology; etnologija; folklorizem; javne prireditve; festivali; Slovenia; Slovenija